2006
DOI: 10.1063/1.2173550
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vacancy Defects in Electroplated Cu Films by Positron Annihilation and its Impact on Stress Migration Reliability

Abstract: Articles you may be interested inVacancy reactions near the interface between electroplated Cu and barrier metal layers studied by monoenergetic positron beams Room-temperature microstructural evolution of electroplated Cu studied by focused ion beam and positron annihilation lifetime spectroscopy Defects introduced into electroplated Cu films during room-temperature recrystallization probed by a monoenergetic positron beam J. Appl. Phys. 98, 043504 (2005); 10.1063/1.2009813 Vacancy-type defects in electroplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
(15 reference statements)
0
2
1
Order By: Relevance
“…7 The poor stress migration performance for the "doped" Cu in this study appears to contradict the trend found by Suzuki et al, where Cu having a relatively higher level of impurities showed fewer stress migration failures compared a "low impurity" Cu. 8 But in Reference 8, the "low impurity" chemistry showing higher stress migration failure rates had S and Cl impurity levels in blanket Cu films of about ∼10 16 atom/cm 3 , about a factor of 10 lower than that found for the "pure" Cu in the current study. As the time to fail is also not specified in Reference 8, the trend found by Suzuki et al does not necessarily conflict with the current results.…”
Section: Electrodepositedcontrasting
confidence: 64%
See 1 more Smart Citation
“…7 The poor stress migration performance for the "doped" Cu in this study appears to contradict the trend found by Suzuki et al, where Cu having a relatively higher level of impurities showed fewer stress migration failures compared a "low impurity" Cu. 8 But in Reference 8, the "low impurity" chemistry showing higher stress migration failure rates had S and Cl impurity levels in blanket Cu films of about ∼10 16 atom/cm 3 , about a factor of 10 lower than that found for the "pure" Cu in the current study. As the time to fail is also not specified in Reference 8, the trend found by Suzuki et al does not necessarily conflict with the current results.…”
Section: Electrodepositedcontrasting
confidence: 64%
“…5,6 Stress migration (sometimes referred to as stress induced voiding), a failure mode where voids in plated Cu coalesce in a line or wide plate beneath a narrow via at elevated temperatures, 7 has been shown to be sensitive to the impurity content of the electrodeposited Cu. 8 An example of such a defect is shown in Figure 1; this type of metallization failure is especially problematic, since the void typically spans the entire via width, breaking electrical continuity. Hence, a detailed understanding of the behavior of impurities over a range of damascene features sizes is required to engineer interconnect microstructure for optimum yield and reliability performance.…”
mentioning
confidence: 99%
“…Control of impurity levels is important in that an excessive impurity content may adversely affect plated Cu stability during subsequent damascene processing steps (e.g., during chemical mechanical polishing or CMP) (5)(6). Stress migration (sometimes referred to as stress induced voiding), a failure mode where voids in plated Cu coalesce in a line or wide plate beneath a narrow via at elevated temperatures (7), has been shown to be sensitive to the impurity content of the electrodeposited Cu (8). An example of such a defect is shown in Figure 1; this type of metallization failure is especially problematic, since the void typically spans the entire via width, breaking electrical continuity.…”
Section: Introductionmentioning
confidence: 99%